Serum Susceptibility in Clinical Isolates of Burkholderia Cepacia Complex Bacteria: Development of a Growth-Based Assay for High Throughput Determination - Zlosnik, James E.; Gunaratnam, L. Cynthia; Speert, David P. (Frontiers in Cellular and Infection Microbiology, 2012)
Burkholderia cepacia complex (BCC) bacteria can cause devastating chronic infections in people with cystic fibrosis (CF). Of particular concern is ‘cepacia syndrome’, a rapidly progressive and usually fatal decline in health, characterised by a necrotizing bacteremic pneumonia. An important component of defence against blood stream infections is the bactericidal action of serum. Traditional methods to determine the capacity of bacterial isolates to resist the bactericidal effects of serum are relatively low throughput, viability assays. In this study, we developed a novel growth-based assay for serum susceptibility, which allows for high throughput analysis. We applied this assay to a range of clinical isolates of BCC and found no direct link between the mucoid phenotype and susceptibility to the inhibitory effects of serum. Of particular clinical significance, we also found no direct link between the last isolate from patients who subsequently developed ‘cepacia syndrome’ and its capacity to resist the inhibitory effects of human serum, indicating serum resistance cannot be used as a marker of an isolate’s capacity to escape from the lung and cause bacteremia.